“Karlsson”, The Amiable Spy: Swedish experiences of Allied espionage and sabotage during World War II - Victor Lundberg (Diacronie. Studi di Storia Contemporanea, 2016)
This article deals with an active personality in the European World War II-context, the Englishman and diplomat Peter Tennant. Officially, he served as press attaché at the British legation in Stockholm and become a popular companion in the capital’s conviviality with a significant social network. Unofficially, he was called “Karlsson” and led the Swedish section of Special Operations Executive, S.O.E. In this role he organized clandestine espionage and sabotage against German interests. This article primarily uses previously confidential archival sources from the civil Swedish counter-espionage to find out more about Tennant’s activities in Sweden during the war and what kind of spy he actually was.